1999
DOI: 10.1146/annurev.immunol.17.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Origins of Immunological Competence

Abstract: Work done in the late 1950s and in the 1960s revealed the role of the thymus in virus-induced leukemia in mice. Thymectomizing mice at birth to test whether the virus first multiplied in thymus tissue and then spread elsewhere ultimately led to the conclusion that the thymus was essential to the normal development of the immune system. Subsequent testing to try to understand how the thymus contributes to the pool of immunocompetent lymphocytes opened a new chapter in immunology and required a reappraisal of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…The thymus, the topic of this article, has interested me since I first heard Jacques Miller discuss his work in 1965 in Brisbane while I was a medical student. Miller is revered for first demonstrating that the thymus produces T cells, but it is often forgotten that he also provided convincing evidence that the thymus is a crucial site for tolerance induction; thus, he showed that strain A T cells arising in a strain B thymus graft displayed skin graft tolerance to B (as well as A) but not to C (1). Proof that thymic tolerance reflects clonal deletion came 25 years later from the crucial studies of the Kappler/Marrack lab on superantigens (2).…”
Section: Prologue (By J Sprent)mentioning
confidence: 99%
“…The thymus, the topic of this article, has interested me since I first heard Jacques Miller discuss his work in 1965 in Brisbane while I was a medical student. Miller is revered for first demonstrating that the thymus produces T cells, but it is often forgotten that he also provided convincing evidence that the thymus is a crucial site for tolerance induction; thus, he showed that strain A T cells arising in a strain B thymus graft displayed skin graft tolerance to B (as well as A) but not to C (1). Proof that thymic tolerance reflects clonal deletion came 25 years later from the crucial studies of the Kappler/Marrack lab on superantigens (2).…”
Section: Prologue (By J Sprent)mentioning
confidence: 99%
“…Almost half a century ago, a series of neonatal thymectomy experiments in mice performed by Jacques Miller identified the function of the thymus as the generative organ for one of the two major classes of lymphocytes, dubbed accordingly thymus derived or T lymphocytes (1). Since this fundamental discovery, a complex picture of the fascinating process of T‐cell development in the thymus has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…The thymus plays a critical role in the development of normal immune tolerance 1. As well as negatively selecting potentially autoreactive T cells, it also positively selects the naturally occurring regulatory T cell subset (T Reg ) (CD4 + FOXP3 + ) 2.…”
mentioning
confidence: 99%